2021
DOI: 10.3389/fpls.2021.727734
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cytogenetic Identification of a Novel Wheat–Thinopyrum ponticum 1JS (1B) Substitution Line Resistant to Powdery Mildew and Leaf Rust

Abstract: Thinopyrum ponticum (2n = 10x = 70) is a wild relative of wheat with high tolerance to both biotic and abiotic stresses; it has been wildly used in wheat genetic improvement. A disomic substitution line named SN19647 was derived from a cross between Triticum aestivum and the wheat–Th. ponticum partial amphiploid SNTE20 (2n = 8x = 56). It was evaluated for disease resistance and characterized via sequential fluorescence in situ hybridization (FISH)-genomic in situ hybridization (GISH) and molecular markers. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The elite cultivars, such as Xiaoyan 6, Gaoyou 503, Xiaoyan 60, and Xiaoyan 81, were widely planted in China and had played an important role in wheat production (Li et al, 2015;Luo et al, 2021;Yang et al, 2022). Meanwhile, numerous chromosome engineering materials were generated, including partial amphiploids (Zheng et al, 2015), additions (Li et al, 2016), substitutions (Wang et al, 2019;Li et al, 2021), translocations (Yang et al, 2022) and introgression lines (Zhan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The elite cultivars, such as Xiaoyan 6, Gaoyou 503, Xiaoyan 60, and Xiaoyan 81, were widely planted in China and had played an important role in wheat production (Li et al, 2015;Luo et al, 2021;Yang et al, 2022). Meanwhile, numerous chromosome engineering materials were generated, including partial amphiploids (Zheng et al, 2015), additions (Li et al, 2016), substitutions (Wang et al, 2019;Li et al, 2021), translocations (Yang et al, 2022) and introgression lines (Zhan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridization is a visual and accurate technique that is widely used in wheat distant hybridization ( Metzlaff et al., 1986 ; Rayburn and Gill, 1987 ; Yang et al., 2015 ; Zhang et al., 2017a ; Li et al., 2021 ). Genomic DNA of L. mollis and P. huashanica were usually used as GISH probe to identify the introduced L. mollis chromosome in wheat background ( Yang et al., 2014a ; Zhang et al., 2017a ; Feng et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…[40]. Wheat distant hybridization is a long-standing and increasingly important method to improve the genetic diversity of common wheat by introducing bene cial genes from related species of wheat [22,41]. Using distant hybridization and conventional breeding, Wang et al have introduced Fhb7 into diverse wheat backgrounds for wheat improvement in wheat and was validated by genomic in situ hybridization [42].…”
Section: Discussionmentioning
confidence: 99%
“…The relative plant of wheat, living in the natural environment for a long time, has been tested by all kinds of terrible environmental conditions, and has a lot of excellent genes and traits which were not possessed or have been lost in common wheat. Introduction of elite genes from wheat relatives into common wheat that is an important way to increase wheat genetic diversity, broaden the genetic basis of wheat breeding and improve wheat varieties [22][23][24][25]. In 2002, Zeller et al found the powdery mildew resistance gene Pm29 in Ae.…”
Section: Introductionmentioning
confidence: 99%